The last agent - Dugoni, Robert (Charles Jenkins series, 2020)
"Betrayed by his own country and tried for treason, former spy Charles Jenkins survived an undercover Russian operation gone wrong. Exonerated, bitter, and safe, the retired family man is through with duplicitous spy games. Then he learns of a woman isolated in Moscow's notorious Lefortovo Prison. If it's Paulina Ponomayova, the agent who sacrificed her life to save his, Jenkins can't leave her behind. But there's no guarantee it's her - or proof Paulina is still alive. To find out, Jenkins must return to Russia"--Dust jacket flap.